Simultaneous Quantification of Dexpanthenol and Resorcinol from Hair Care Formulation Using Liquid Chromatography: Method Development and Validation - Amit Kumar De; Partha Pratim Chowdhury; Shyamaprasad Chattapadhyay (Scientifica)
The current study presents the simultaneous quantification of dexpanthenol and resorcinol from marketed hair care formulation. Dexpanthenol is often present as an active ingredient in personal care products for its beautifying and invigorating properties and restorative and smoothing properties. On the other hand resorcinol is mainly prescribed for the treatment of seborrheic dermatitis of scalp. The toxic side effects of resorcinol limit its use in dermatological preparations. Therefore an accurate quantification technique for the simultaneous estimation of these two components can be helpful for the formulation industries for the accurate analysis of their product quality. In the current study a high performance liquid chromatographic technique has been developed using a C18 column and a mobile phase consisting of phosphate buffer of pH = 2.8 following a gradient elution. The mobile phase flow rate was 0.6 mL per minute and the detection wavelength was 210 nm for dexpanthenol and 280 nm for resorcinol. The linearity study was carried out using five solutions having concentrations ranging between 10.34 μg·mL−1 and 82.69 μg·mL−1 (r2=0.999) for resorcinol and 10.44 μg·mL−1 and 83.50 μg·mL−1 (r2=0.998) for dexpanthenol. The method has been validated as per ICH Q2(R1) guidelines. The ease of single step sample preparation, accuracy, and precision (intraday and interday) study presents the method suitable for the simultaneous quantification of dexpanthenol and resorcinol from any personal care product and dermatological preparations containing these two ingredients.